The Covid-19 pandemic and the challenges facing the civil liability of health professionals - Galán Camargo, Viviana (DIXI, 2022)
Subject and scope: A reflection is made on the challenges that the pandemic has generated in the area of medical civil liability. Based on the regulations, the possible scenarios in which health professionals or health facilities would incur in a case of civil liability within this context of covid-19 are determined.Characteristics: In the case of new diseases, the principles of fault liability will prevent medical providers from being condemned for facts or circumstances that could not have been foreseen or avoided according to the state of knowledge of science. In addition, with regard to the public health problem, any judgment of liability should take into account the changes that will occur in the medical lex artis and differentiate the eventual liability of health care providers from that of the authority in charge of controlling the effects of the pandemic.Findings: As everything new is unknown, covid-19 was and will be a learning process in all fields.Conclusions: The health emergency caused by the coronavirus shows that the responsibility regimes must be able to differentiate the conceptual instruments available to deal with a new disease that, in addition, became a pandemic.
Keywords: covid-19; legal practice; surgical instrumentation; pandemic; health professions; civil liability; public health